Development of Emotional Competencies through Outdoor Training. An analysis within the University Context - GÃ³mez, JesÃºs Molina; GÃ¡mez, Manuel Ãngel FernÃ¡ndez; Perez, Ana MarÃa Rosales; Mele, Pere Mercade (Journal of Reviews on Global Economics, 2019)
Among the most recognized management training methodologies is experiential learning which helps managers to develop self-confidence and better understand organizational problems. Until now, there has not being examined how these procedures affect students of Business Management, with no empirical evidence to substantiate the results in this context. This work contributes to a better understanding of how to develop emotional competencies of Management students, based on a review of the literature on emotional competencies, experiential learning and Outdoor Training. The results of this study were obtained through an experimental design pre-test/post-test/re-test with data from 108 students. It was found that most of those who participated in the program of Outdoor Training significantly improved their emotional competencies, both the personal and the social ones.